Analysis of the forest and grassland vegetation at southwestern side of Quezon Protected Landscape, Southern Luzon, Philippines - Santos, Jocelyn M. (Animo Repository, 2016)
Forest supports countless species and plays a significant role in sustaining biological and ecological processes. This paper focused on the trees and grassland vegetation using transect and quadrat sampling techniques to determine the importance values of each species encountered. A total of 35 species of trees belonging to 19 Families were identified at the southwestern side of Quezon Protected Landscape forest. An average density of 0.07 tree/m2 was recorded from the sampling site. Shorea polysperma (Blco.) Merr. was the most dominant species with an importance value of 45.20%. It was followed by Syzygium sp. with importance value of 29.78%, Microcos stylocarpa (Warb.) Burr. with 19.34%. Analysis of the vegetation (grasses, weeds, herbs, and ferns) of the grassland area revealed a total number of 30 species belonging to 16 Families. Species under the Family Leguminosae/Fabaceae was the most abundant across all plots. Wedelia trilobata Hitchc. was the most dominant species with an importance value of 30.80% and having 64 individual species. It was followed by Eleusine indica (L.) Gaertn. with an importance value of 30.31%, Melastoma malabathricum L. with 29.98%, Saccharum spontaneum L. with 28.29%, Imperata cylindrica (L.) P. Beauv. with 27.46% and Lycopodium clavatum L. with 23.68%. Saccharum spontaneum, Melastoma malabathricum, and Imperata cylindrica have the greatest biomass among all species across all plots. The species with the highest importance values are those with highest population density, occupy the largest space and have a high frequency as Shorea polysperma and Wedelia trilobata. Strengthening the conservation efforts is recommended for sustainable management of the landscape